Development of alpha mangostin-PLGA nanoparticles as an anticancer agent - Aimen, Abdo; Mohamed, Farahidah; Bakhtiar, M. Taher (2011)
α-Mangostin, a xanthone which was isolated from Garcinia malaccensis has been documented to exhibit anticancer effects against many cancerous cell lines. Due its high cytotoxicity, this study had attempted to encapsulate the α-mangostin into biodegradable PLGA copolymer using colloidal-extraction solvent evaporation method. Different emulsification process had been investigated. The resultant nanoparticles were characterized for their size distribution and external morphology by laser diffractometry and scanning electron microscope (SEM), respectively. The concentration of entrapped α-Mangostin was determined by HPLC. Our data demonstrated that the encapsulation efficiency was affected by the type of emulsification process. The in vitro anti-cancer activity of α-Mangostin-PLGA nanoparticles was evaluated using lung cancer cell line (A549) and was compared to the free α-Mangostin. Our data revealed that the PLGA nanoparticles loaded with α-Mangostin showed lower cytotoxic effect compared to free α-Mangostin. To conclude, PLGA nanoparticles may be used as a promising micro-carrier system to deliver α-Mangostin for passive targeting to tumors.